Integrated Hydrologic and Hydraulic Analysis of Torrential Flood Hazard in Arequipa, Peru. (14th January 2021) - Mazer, Katy E.; Tomasek, Abigail A.; Daneshvar, Fariborz; Bowling, Laura C.; Frankenberger, Jane R.; McMillan, Sara K.; Novoa, Hector M.; Zeballos‐Velarde, Carlos
Abstract: Seated at the foot of the Misti volcano in an area prone to intense seasonal rains and earthquakes, the city of Arequipa is highly vulnerable to natural disasters. During the rainy season, intense storms create large volumes of runoff that rush through the city's ephemeral streams, known locally as torrenteras . Episodic flows in these torrenteras have caused flooding, damage to bridges, homes, and other infrastructure, and caused many deaths. In recent years, while unprecedented rain events have caused extreme disasters, the city's population has continued to expand into these channels by creating informal or illegal settlements. Currently, detailed hazard maps of flood‐prone areas surrounding the torrenteras are not available to stakeholders in Arequipa. In this study, hydrologic and hydraulic models were combined to assess flash flood hazards, including inundation, velocity hazards, and slope instability hazards. Hydrologic models were created using satellite precipitation data and terrain‐sensitive, gridded climate maps to characterize flow within six torrenteras in Arequipa. These flows were used in conjunction with elevation data and data collected in the field using an online mobile application system to develop a hydraulic model of these flood events. Hydraulic model outputs were used to determine flood hazards related to inundation, velocity affecting human stability, and slope instability in case study areas of the torrenteras . We then discuss how this information can be used by disaster risk management groups, water authorities, planners and municipalities, and community groups.